Answer:
(-12,9)
Step-by-step explanation:
The equation of a circle is given by the equation (x-h)^2 + (y-k)^2 = r^2, where (h,k) is the center point on the graph.
Therefore, in the equation (x+12)^2 + (y-9)^2 = 35, the center point on the graph would be (-12,9).
Answer:
(s-t)(-1) = -1
(s+t)(-1) = -7
Step-by-step explanation:
Given the following set of functions
s(x)=2x-2
t(x)=3x
(s-t)(x) = s(t) - t(x)
(s-t)(x) = 2x - 2 - 3x
(s-t)(x) = -x -2
(s-t)(-1) = -(-1) - 2
(s-t)(-1) = 1-2
(s-t)(-1) = -1
(s+t)(x) = s(t) + t(x)
(s+t)(x) = 2x - 2 + 3x
(s+t)(x) = 5x -2
(s+t)(-1) = 5(-1) - 2
(s+t)(-1) = -5-2
(s+t)(-1) = -7
Essentially 11(4d + 6) = 11*4d + 6*11
44d + 66
Answer:
8
Step-by-step explanation:
=(7−(−1))2+(4−4)2‾‾‾‾‾‾‾‾‾‾‾‾‾‾‾‾‾‾‾‾√
=(8)2+(0)2‾‾‾‾‾‾‾‾‾‾√
=64+0‾‾‾‾‾‾√
=6‾√4
=8